Interactive E-book on Main Ideas and Supporting Ideas in Argumentative Paragraphs - Ni Kadek Sukma Swari; Gusti Ayu Putu Sukma Trisna; Luh Sri Surya Wisma Jayanti (Universitas Pendidikan Ganesha, 2025)
Students' difficulty in understanding the main ideas and supporting ideas in a text results in their low ability to grasp the essence of the reading material. This condition is exacerbated by the limited use of interactive and engaging learning media. This study aims to develop, evaluate the feasibility, and test the effectiveness of interactive e-books in improving students' understanding of main ideas and supporting ideas. The study uses the Research and Development (R&D) method with the ADDIE model and a pre-experimental one-shot case study design. The research subjects were 14 fourth-grade students as test participants. Data were collected through expert validation questionnaires, teacher and student practicality questionnaires, observations, and learning outcome tests. Research instruments included validation sheets, response questionnaires, and evaluation questions. Data analysis was conducted using normality tests and one-sample t-tests. The results of the study indicate that the interactive e-book developed is suitable for use in learning, practical to implement in the classroom, and effective in improving students' understanding of main ideas and supporting ideas. This study concludes that interactive e-books are learning media that can facilitate active learning and support the improvement of students' reading literacy. Implicitly, this e-book can be an alternative solution for adaptive digital media tailored to students' needs.